Reading Attitudes of Fourth Year English as a Foreign Language Students - Mata Boschini, Laura Paola (2023)
The present exploratory study sought to identify the attitudes towards reading for pleasure of a group of fourth year English as a Foreign Language (EFL) majors after taking mandatory literature courses. A total of 45 students from the School of Modern Languages at a public university in San José, Costa Rica participated in this investigation. In order to elicit the participants’ attitudes and motivations both before and after entering the university, an online survey was administered. The results of the survey showed that after entering the university almost half of the participants kept good reading habits, apart from the mandatory readings. Main findings also reveal that the main pre-university reading motivators suffered a change after entering the university. Although personal enjoyment and relaxation were maintained, motivators related to the general improvement of language skills obtained a higher relevance for the students. The survey answers also suggested the literary works read in class play an important role in the students’ voluntary reading practices. Practical implications are discussed.